Bioinformatic Analysis of C1GALT1 in Cancer: Insights Into Prognosis, Metastasis and Therapeutic Potential - Ecem Kalemoglu; Ayse Caner (Cancer Reports)
ABSTRACT Background This study evaluates the expression, regulation, and clinical relevance of C1GALT1, a key enzyme in mucin‐type O‐glycosylation, across a broad spectrum of human cancers. Aberrant glycosylation is a well‐established hallmark of malignancy, contributing to tumor growth, immune evasion, and metastasis. C1GALT1, also known as core 1 β1,3‐galactosyltransferase or T‐synthase, catalyzes the formation of the core 1 O‐glycan structure and requires the chaperone Cosmc for proper folding and activity. While previous studies have implicated C1GALT1 in cancer progression, a systematic pan‐cancer analysis exploring its gene expression patterns, epigenetic regulation, immune interactions, and prognostic significance has not been fully elucidated. Aims This study aims to computationally investigate C1GALT1 expression, regulation, and clinical relevance across multiple cancers using TCGA datasets to evaluate its potential as a biomarker and therapeutic target. Methods We conducted a comprehensive bioinformatic analysis of C1GALT1 using publicly available datasets from The Cancer Genome Atlas (TCGA). Gene expression, DNA methylation, and survival analyses were performed, along with correlation analyses between C1GALT1 and proliferation‐ or metastasis‐related genes, Cosmc expression, and immune cell infiltration (specifically, regulatory T‐cells [Tregs] and myeloid‐derived suppressor cells [MDSCs]), using transcriptomic web platforms. Results C1GALT1 expression was significantly upregulated in gastrointestinal and genitourinary cancers compared to normal tissues, while downregulated in thyroid, breast, and prostate cancers. Elevated expression correlated with reduced overall survival in lung, bladder, liver, and glioma/glioblastoma. DNA methylation analysis showed an inverse correlation between methylation and expression levels in multiple cancer types. C1GALT1 expression positively correlated with Cosmc, proliferation markers (MKI67, PCNA, MCM family, PLK1), and several metastasis‐associated genes. Immune profiling revealed context‐dependent correlations: C1GALT1 negatively correlated with Tregs and MDSCs in gastrointestinal cancers but positively in lung, breast, and prostate cancers. Conclusion Our pan‐cancer analysis suggests that C1GALT1 is differentially expressed and epigenetically regulated across tumor types and may contribute to tumor proliferation, metastasis, and immune modulation. While these findings support C1GALT1 as a potential biomarker and therapeutic target, further in vitro and in vivo studies are necessary to validate its mechanistic roles and clinical utility.